2015
DOI: 10.9734/bjmmr/2015/19965
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Benign Prostatic Hyperplasia and International Prostatic Symptom Score

Abstract: Benign prostatic hyperplasia is the most common prostatic pathology and its incidence has accelerated recently [1]. Benign prostatic hyperplasia (BPH) is diagnosed histologically as enlargement of mucosal and sub mucosal glands with the proliferation of prostatic stroma occurring within the prostatic transition zone [2]. BPH compresses the urethra resulting in anatomic benign prostatic obstruction and may present as lower urinary tract symptoms (LUTS). The prevalence of LUTS can be progressive in the aging mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…97.3 percent of the patients in the present study complaint of lower urinary tract symptoms with or without hematuria, in 2015 Raza et al 8 also published a similar study in which they found lower urinary tract symptoms as most common presenting symptom.…”
Section: Discussionsupporting
confidence: 63%
“…97.3 percent of the patients in the present study complaint of lower urinary tract symptoms with or without hematuria, in 2015 Raza et al 8 also published a similar study in which they found lower urinary tract symptoms as most common presenting symptom.…”
Section: Discussionsupporting
confidence: 63%
“…Obstructive LUTS in prostatomegaly is due to compression of the prostatic urethra. Aslamet al [13] and Raza et al [14] also found LUTS as the most common presenting symptom correlated with our study.…”
Section: Discussionsupporting
confidence: 90%
“…The total score ranges from 0 to 35 (asymptomatic to symptomatic) (9) . The Symptom index is categorized as mild (≤7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and severe (≥20). For symptomatic score classification, IPSS divides the symptoms into obstructive and irritative symptoms as assessed by questionnaire (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Voiding symptoms are incomplete emptying, intermittency, weak stream and straining. Benign Prostatic Hyperplasia has been used to explain a group of obstructive and storage symptoms (11,12) ". This study was conducted to identify that among IPSS, which of the following symptoms whether obstructive/ voiding and irritative/storage were more closely linked with BPH patients.…”
Section: Introductionmentioning
confidence: 99%